Influence of the organizational structure in the organizational learning capacity: the case of a world manufacturer of commercial vehicles - Hörbe, Tatiane de Andrade Neves; Moura, Gilnei Luiz de; Machado, Emanuelly Comoretto; Campos, Simone Alves Pacheco de (Revista de Administração da UFSM, 2021)
Purpose – This study aims to analyze the influence of the dimensions of the organizational structure on the organizational learning capacity in a transport company. Design/methodology/approach – For this, we adopted as a research design the method of case study and for data collection and analysis, using the quantitative and qualitative procedures. For the purposes of this study, the choice was made of the Administrative Unit of Construction Equipment of a worldwide manufacturer of commercial vehicles. Findings – Among the results it was verified that: (i) an environment conducive to organizational learning must be supported by organizational organizational structures; (ii) the dimensions of centralization and integration when working in congruence tend to reinforce processes and levels of learning; (iii) the high degree of formalization has no influence on organizational learning capacity. Research limitations/implications – As limiting factors of the research, the cross-sectional approach is considered to study the theme of organizational learning. Still, the data collection in only one Unit of the company Alpha, the number of interviews carried out and the fact that it involves only managers from the commercial and sales sectors. Practical implications – The dimensions Centralization and Integration influence the Capacity for Organizational Learning. Originality/value – In order to develop an environment conducive to organizational learning, organizations should make use of more flexible structural forms, which encourage people's autonomy and freedom through decentralization. Also, that organizations seek a high level of integration, information sharing and that communication is fluid throughout the company.